Diagnosis to develop a model that allows the formalization of informal collection centers for segregated waste, in the district of Ate (Lima, Peru) - Urbay Paz, Sergio César (2022)
The general objective of this research, done in 2020, was to analyze the effect of the formalization model on the application of waste segregation methods in informal collection centers, located between kilometers 16 and 17.5 of the Ate district, (Lima, Perú). The methodological design for developing the thesis project was of the "action-research" type in which a mixed qualitative-quantitative approach was used, through surveys and interviews to workers of informal collection centers, recyclers, area residents and Ate municipality professional experts in solid waste management. Through the results, we propose a formalization model with methods that help to carry out adequate waste segregation in informal collection centers, incorporating a comprehensive management system in each of them.